Pelatihan Peningkatan Literasi Keuangan Syariah Pada Siswa SMA IT Al-Utsaimin Bangkinang - Khairi, Rifqil; Mairiza, Diany; Hasda, Mifta; Hidayat, Hidayat; Reza, Saru; Syaipudin, Muhammad (Journal of Community Sustainability, 2025)
This community service is carried out for SMA IT Al Utsaimin Bangkinang students, the purpose of this community service is to find out about Sharia Contract Education and the Development of Sharia Economics for SMA IT Al Utsaimin Bangkinang students. The methods used in this community service activity are counseling, presentations and discussions. The results of the community service show that: The community service program for SMA IT Al Utsaimin Bangkinang students can be organized well and run smoothly according to the activity plan that has been prepared, the results of this community service concluded that: First, SMA IT Al Utsaimin Bangkinang students, some already understand, some are still hesitant, some even do not understand, Second, The achievement of the objectives of the community service program for SMA IT Al Utsaimin Bangkinang students, the entire program that has been carried out with collaboration between business owners and community service workers has been carried out all and in accordance with the event rounddown and the time that has been determined previously.